2018
DOI: 10.4172/2155-9546.1000522
|View full text |Cite
|
Sign up to set email alerts
|

pH Characterization of Digestive Enzyme and In vitro Digestibility of Red Bee Shrimp Caridina cantonensis (Decapoda: Atyidae)

Abstract: The characteristics of digestive enzyme from red bee shrimp (Caridina Cantonensis), a tiny ornamental shrimp, were investigated under various pH ranging from 2 to 12. The aim of this study was to find out the specific activities of protease, amylase, lipase, cellulose, trypsin and chymotrypsin and in vitro raw materials by shrimp enzyme digestibility. Fifteen and sixty-day old shrimp were obtained from private farms in Bangkok, Thailand. Protease, lipase, amylase, cellulase, trypsin and chymotrypsin specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Subsequently, the contents were homogenized and centrifuged at 4°C at (0.13416 g ) for 15 min. After this step, the supernatant was collected and kept at −20°C until for digestive enzyme activity assays (Kattakdad et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the contents were homogenized and centrifuged at 4°C at (0.13416 g ) for 15 min. After this step, the supernatant was collected and kept at −20°C until for digestive enzyme activity assays (Kattakdad et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…To date, a lack of study distinguishes whether the activity arising from the exogenous enzymes is directly contributed by probiotics or indirectly through inducing the endogenous enzymes produced by the host [222,395] . Usually, enzymatic activity improvement is assayed using the pooled gastrointestinal samples or whole-body extract of shrimps [33,104,182,211,387,393,395,407] . Ziaei-Nejad et al [387] reported that Bacillus sp.…”
Section: Increasing the Digestive Enzyme Activitymentioning
confidence: 99%
“…The digestive enzymes identified in shrimps include proteases (aminopeptidase, carboxypeptidase, chymotrypsin, metalloprotease, trypsin), lipase, esterase, and carbohydrase (amylase, cellulase and chitinase) [222,238,407,409,410] . Despite being an omnivorous animal, shrimp has a limited capacity to digest some forms of complex carbohydrates like starch due to the lack of specific enzymes such as the α-1,6-glucosidase.…”
Section: Increasing the Digestive Enzyme Activitymentioning
confidence: 99%